Surgical management of bilateral horizontal mandibular canine impaction: case report - Julia, Vera; Arlen, Antonius Kevin; Wijaya, Arbi; Reksoprodjo, Muhammad Ramaditto; Sulistyani, Lilies Dwi; Ratman, Mohammad Farid (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
Introduction: Mandibular canine impaction is one of the most complex dental anomalies. The low incidence rate of mandibular canines impaction resulted in the unavailability of guidelines for managing impacted mandibular canines, especially bilateral horizontal cases. This case report describes a surgical procedure to manage bilateral horizontal mandibular canines impaction. Case report: A 14-year-old girl with bilateral horizontal mandibular canines impaction was referred from the orthodontics department. The orthopantomograph (OPG) radiograph shows there was bilateral horizontal mandibular canines impaction near premolars root apices. The patient went for surgical removal in general anesthesia for the impacted canines. Odontectomy was performed by separating the tooth into several fragments. A three months follow-up showed there was no post-operative complaint. Conclusion: Odontectomy of bilaterally impacted mandibular canines can be done to avoid interference with orthodontic treatment. Keyword : Bilateral horizontal canine impaction, odontectomy, oral surgery Penatalaksanaan kasus impaksi kaninus bilateral horizontal mandibula secara bedah: laporan kasusABSTRAKPendahuluan: Impaksi kaninus bilateral mandibula adalah salah satu bentuk kompleksitas kelainan gigi. Insidensi yang rendah pada kasus impaksi kaninus bilateral mandibula menyebabkan ketiadaan petunjuk untuk penatalaksanaan bedah pada kasus yang serupa, terutama pada kasus bilateral. Laporan kasus ini bertujuan mendeskripsikan prosedur pembedahan pada kasus impaksi kaninus bilateral mandibula. Laporan kasus: Perempuan berusia 14 tahun dengan impaksi kaninus bilateral mandibula dirujuk dari departemen ortodonsia. Radiografi panoramik meununjukkan terdapat impaksi kaninus bilateral dengan tipe horizontal, berdekatan dengan ujung akar premolar. Pasien dilakukan ekstraksi gigi impaksi kaninus dalam anestesi umum dengan metode pembelahan gigi menjadi beberapa fragmen. Pada kontrol tiga bulan selanjutnya tidak terdapat keluhanan pascaoperasi. Simpulan: Odontektomi pada kasus impaksi kaninus bilateral mandibula dapat menjadi opsi untuk mencegah gangguan dalam perawatan ortodonti.Kata kunci: Impaksi kaninus bilateral horizontal, odontektomi, bedah mulut